SAT0724-HPR Gothenburg nurse led tight control study – gotnet. patients' experiences of nurse-led care and tight control. a qualitative study of patients with rheumatoid arthritis. (15th June 2017) - Bergsten, U; Sjö, A-S
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory illness, using both pharmacological and non-pharmacological therapies. Some patients experience good treatment, knowledge about their illness and situation. For other patients, it might look different depending on how much they know about their illness. Earlier research has primary focused on patients in remission. In order to strengthen and support patients with RA that are not feeling well, to give them more knowledge about their situation, one strategy could be that they have access to a nurse-led rheumatology clinic with person-centered care (PCC). Objectives: The aim of this study was to describe patients' experiences of nurse-led care tight control. Methods: Qualitative design was used in order to receive deeper understanding of the phenomenon. Interviews were conducted with 12 informants (with strategic sample) that participated in the intervention group of a randomized controlled trial exploring the effect of patient centered care, the Got-Net study. The interviews were analyzed using phenomenography approach. Results: The informants' experiences of nurse-led care tight control emerged in three categories. The three categories describe the process, the relationship between the concepts. The first step describes the Meeting of competence, the next step that the informant experienced was Relationship building and the last step to have Made a personal journey . Conclusions: Patients with RA who got the opportunity of nurse-led care and tight control became strengthen, got extended knowledge about their illness. Patients have been treated on their own level, knowledge and needs, by using a person-centered approach. Disclosure of Interest: None declared